Responding to the potential environmental impact to extend battery life: Preliminary study of informal actors' readiness - Annie Purwani; Siti Mahsanah Budijati; Hayati Mukti Asih; Tatbita Titin Suhariyanto; Choirun Nisa (Jurnal Sistem dan Manajemen Industri, 2025)
The increasing number of electric motorcycles in Indonesia has created new challenges related to battery waste management, potentially impacting human health, the environment, and resource scarcity. This study aims to assess the potential life cycle impacts of a 1.0 kWh electric motorcycle battery product system under repair treatment for two widely used battery types: NMC and LFP. The study used a Life Cycle Assessment (LCA) method with gate-to-gate assessment. The assessment results for both battery types with repair treatment had the greatest impact on the midpoint of freshwater eutrophication. Based on the normalized results of the five impact categories assessed, the repair treatment on LFP type batteries showed better environmental performance than the NMC type. The balancing process was found to have the greatest environmental impact for both battery types. This study confirms that recycling management by informal actors is a significant solution. The repair treatment solution contributes to providing benefits in extending the battery life cycle and does not have the potential for significant environmental impacts.